Inventer, prouver, convaincre dans Origen de la Casa de Granada (manuscrit 9/195, bibliothèque de l’Académie Royale d’Histoire de Madrid) - Frédéric Alchalabi (Atalaya)
Origen de la Casa de Granada can be read in a manuscript kept in the library of the Royal Academy of History in Madrid. The author of the book relates the story of the ancestors of the morisco family Granada Venegas, from Granada. The purpose of the author of Origen de la Casa de Granada is double: to present the Alnayar — the Muslim ancestors of the Granada Venegas family — as the legitimate heirs to the throne of Granada and deny the rights of the Alhamar dynasty; to prove that the Alnayar have regularly collaborated with the Christian princes of the Iberian peninsula, and in particular with the Castilian kings. In order to do so, the writer takes ownership of the testimonies of other authors, historiographers but also well-known or competent people ready to take on the responsibility for the laudatory discourse on the Granada Venegas family.